Search for a narrow charmed baryonic state decaying to D*(+/-)p(-/+) in ep collisions at HERA - Chekanov, S; Derrick, M; Loizides, J; Magill, S; Miglioranzi, S; Musgrave, B; Repond, J; Yoshida, R; Mattingly, M; Pavel, N; Antonioli, P; Bari, G; et al. (2004)
A resonance search has been made in the D*±p∓ invariant-mass spectrum with the ZEUS detector at HERA using an integrated luminosity of 126 pb-1. The decay channels D*+ -→ D0πs+ → (K -π+)πs+ and D*+ → D0πs+ → (K-π+π+π-) πs+ (and the corresponding antiparticle decays) were used to identify D*± mesons. No resonance structure was observed in the D*± p∓ mass spectrum from more than 60 000 reconstructed D*± mesons. The results are not compatible with a report of the H1 Collaboration of a charmed pentaquark, Θc0. © Springer-Verlag / Società Italiana di Fisica 2004.